# Alternating sum of binomial coefficients is equal to zero [duplicate]

Prove without using induction that the following formula:$$\sum_{k=0}^n (-1)^k\binom{n}{k}=0$$ is valid for every $n\ge1$.

### Progress

For each odd $n$ we can use the identity:$$\binom{n}{k}=\binom{n}{n-k}$$ In fact all terms equidistant from the end points are opposite. My question is: if $n$ is even how can we prove it?

## marked as duplicate by lab bhattacharjee calculus StackExchange.ready(function() { if (StackExchange.options.isMobile) return; $('.dupe-hammer-message-hover:not(.hover-bound)').each(function() { var$hover = $(this).addClass('hover-bound'),$msg = $hover.siblings('.dupe-hammer-message');$hover.hover( function() { $hover.showInfoMessage('', { messageElement:$msg.clone().show(), transient: false, position: { my: 'bottom left', at: 'top center', offsetTop: -7 }, dismissable: false, relativeToBody: true }); }, function() { StackExchange.helpers.removeMessages(); } ); }); }); Aug 24 '14 at 16:09

• Depending on your perspective, this fact shows that the Euler characteristic of the $n$-torus $T^n = (S^1)^n$ is zero, or it can be proven using that $\chi(T^n) = 0$. – Phillip Andreae Aug 24 '14 at 16:18
Set $a=1,b=-1$ in the Binomial Expansion formula for non-negative intger $n$ $$(a+b)^n=\sum_{k=0}^n\binom nk a^{n-k}b^k$$